Buku Tamu Perpustakan Berbasis Website Dengan Metode Agile (Perpustakaan Badan Pusat Statistik Kabupaten Brebes) - Suci, Ika Rahmawati; Prasetyo, Novian Adi; Fitriana, Gita Fadila (LPPM STT Terpadu Nurul Fikri, 2021)
The design of the library guestbook dashboard system at BPS assists in processing visitor data on the processing staff by providing an information system in the form of a website in the processing section. Visitors fill out their bio by the guidelines by utilizing the website on the device. This website makes with a hypertext preprocessor (PHP) programming language that uses databases as a data processing medium. PHP uses MYSQL as a database. The method used to make a website is agile. In this study, data collection conducts by interviewing the BPS sources of Brebes Regency. In this study, researchers found problems in recording guest data of the BREBES Regency BPS library using stationery. Agile methods can do in the creation of this website with results by the requests of BPS staff of Brebes Regency for the creation of a guest book website of the LIBRARY bps Brebes regency has been tested using black box testing methods through google meet media and testing directly with participants of 7 processing staff. From the results of black box testing, 100% of respondents answered that all functional aspects of the BPS library guest book website system developed can function by the design and needs of the system.